“Agrarian Unrest” in Central Black Earth Region in Autumn 1905 - V. A. Ippolitov (Научный диалог)
The study draws on documents from the first department of the Ministry of Justice regarding "agrarian unrest" in the Central Black Earth region in autumn 1905, housed in the Russian State Historical Archive. Cases related to agrarian uprisings in the Tambov and Voronezh gubernias are examined, with a focus on studying the involvement of peasants from the "revolutionary generation" in the agrarian movement (individuals born approximately in the 1890s). The significant role of rumors during the revolution is highlighted. The author explores the causes, algorithms, and characteristics of peasant uprisings, analyzing the role of "leaders" in "agrarian unrest," often led by young individuals less inclined to adhere to traditions. The leading role of youth in the revolutionary movement is emphasized, with urban disturbances acting as catalysts for agrarian uprisings. The communal role is evident in preparing and carrying out forest clearances, pogroms, and more. The evolution of the mosaic nature of peasant self-awareness during the "revolutionary generation" period is analyzed. The author concludes that the October 17, 1905 manifesto played a significant role in awakening revolutionary consciousness in the Tambov and Voronezh villages. Shortcomings in investigating cases of "agrarian unrest" are discussed, allowing many rebels to evade punishment, with the average age of accused peasants calculated at 35.6 years.